2019
DOI: 10.3390/ani9080547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation with Trimethylglycine (Betaine) and/or Vitamins on Semen Quality, Fertility, Antioxidant Status, DNA Repair and Welfare of Roosters Exposed to Chronic Heat Stress

Abstract: In this study, we investigated the influence of betaine (Bet, 1000 mg/kg), with or without vitamin C (VC, 200 mg/kg ascorbic acid) and/or vitamin E (VE, 150 mg/kg α-tocopherol acetate) on semen quality, seminal and blood plasma constituents, antioxidants’ status, DNA repair, and the welfare of chronic heat stress (CHS)-exposed roosters. A total of 54 roosters were divided into six groups of nine replicates. One group was kept under thermoneutral conditions, whereas the other five were kept under CHS. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…In laying hens, supplementing betaine (1000 mg/kg of feed) along with vitamin C (200 mg/kg of feed) improved laying performance during the chronic heat stress [ 125 ]. In roosters, supplementation of betaine (1000 mg/kg of feed) improved sperm concentration and livability, seminal plasma total antioxidant capacity, fertility, and welfare under chronic heat stress [ 126 ].…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%
“…In laying hens, supplementing betaine (1000 mg/kg of feed) along with vitamin C (200 mg/kg of feed) improved laying performance during the chronic heat stress [ 125 ]. In roosters, supplementation of betaine (1000 mg/kg of feed) improved sperm concentration and livability, seminal plasma total antioxidant capacity, fertility, and welfare under chronic heat stress [ 126 ].…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%
“…Proper nutrition can help in maintaining immune systems as the frontline of defense. Researchers have believed that the deficiency of a particular nutritional element is implicated in the impaired immune responses ( 6 , 11 , 185 , 186 ). Nutrition principles based on using some dietary substances such as trace elements, vitamins, probiotics, and nutraceuticals may be helpful in the possible prevention and management of COVID-19 ( 187 ).…”
Section: Past Experience Current Situation and Future Prospectivementioning
confidence: 99%
“…With regarding arginine level in the diet, supplying sufficient methyl donors such as methionine or betaine in accordance with that, is necessary and each failure into accomplishing can significantly impact performance (Keshavarz and Fuller 1971). Attia et al (2019) with betaine and Attia et al (2012Attia et al ( , 2013 with acetic acid showed improved performance and tolerance to heat stress due to their supplementation. Therefore, the purpose of this study was to elucidate the effects of differing levels of GAA on egg production, antioxidant status, nutrient digestibility and intestinal morphology in laying Japanese quails.…”
Section: Introductionmentioning
confidence: 99%